Providing multicast through recursive unicast. - Zhang, Baoxian (IEEE Communications magazine)
The group addressing model currently employed for supporting IP multicast has caused several implementation issues including global unique address allocation, sender admission control, and multicast forwarding state scalability. In this article we first review related work carried out to address these issues using different mechanisms and at different levels. We discuss their merits and deficiencies and also their possible combinations for improved performance. We then devise a protocol that works by introducing the idea of recursive unicast into an existing multicast routing protocol, multicast extension to OSPF (MOSPF), to achieve scalable multicast. Simulation results are used to demonstrate the high performance of the devised protocol in reducing computational overhead and forwarding state at routers and also in casing address allocation and admission control.